ANALYSIS OF THE EFFECTIVENESS OF THE PROVISION OF INFORMATION SYSTEMS SERVICES BASED ON THE CONCEPT OF SERVICE-ORIENTED ARCHITECTURE (Euro-Asia Conferences, 2021)
A method of presenting the services and resources of systems based on the concept of service-oriented architecture is proposed, the effectiveness of which is determined by simulation